Monetary Favors and Their Influence on Neural Responses and Revealed Preference - Harvey, Ann H. (Society for Neuroscience, 2010)
Favors from a sender to a receiver are known to bias decisions made by the recipient, especially when the decision relates to the sender, a feature of social exchange known as reciprocity. Using an art-viewing paradigm possessing no objectively correct answer for preferring one piece of art over another, we show that sponsorship of the experiment by a company endows the logo of the company with the capacity to bias revealed preference for art displayed next to the logo. Merely offering to sponsor the experiment similarly endowed the gesturing logo of the company with the capacity to bias revealed preferences. These effects do not depend upon the size of the displayed art or the proximity of the sponsoring logo to the piece of art. We used functional magnetic resonance imaging to show that such monetary favors do not modulate a special collection of brain responses but instead modulate responses in neural networks normally activated by a wide range of preference judgments. The results raise the important possibility that monetary favors bias judgments in domains seemingly unrelated to the favor but nevertheless act in an implicit way through neural networks that underlie normal, ongoing preference judgments.